The growth of beach fale accommodation in Samoa: Doing tourism the Samoan way - Scheyvens, Regina (Massey University, 2009)
Samoa is an independent Pacific Island nation with beautiful beaches, rainforests and volcanic features, and is home to vibrant Polynesian communities living mainly in picturesque villages dotted around two main islands. It is seemingly another perfect island paradise, yet Samoans have a long history of resistance to outside interference thus in the past they have been reluctant to trade on their country’s natural beauty and cultural features by encouraging tourism development. Threats to the country’s agriculture sector from two cyclones and a taro blight led to a change of heart in the early 1990s, and tourism has since rapidly grown to become Samoa’s main industry, contributing four times more to the economy than agriculture (Twining-Ward and Twining-Ward, 1998). Arrivals grew from less than 48,000 in 1990 to over 92,000 by 2003. However, unlike the three most popular Pacific Island destinations, Fiji, French Polynesia and New Caledonia, Samoa is not home to numerous large resorts. Instead the tourism industry here is dominated by small to medium sized enterprises which are mostly under local ownership and control. The largest growth in recent years has been experienced in the budget beach fale accommodation sector. Beach fale, or traditional beach huts, are now a strong feature of the coastal landscape of Samoa. A family or community need relatively little capital to establish a beach fale operation, but the family or community group does need permission from the relevant matai (chiefs). These fale range from basic, open sided huts with thatched roofs and traditional woven blinds in the place of walls, to walled bungalows with small verandas. Bathroom and dining facilities are shared with other guests, and the relations between guests and those catering to their needs are more friendly than servile. Guests are expected to conform with cultural protocol during their stay, which includes dressing appropriately when entering a village and respecting Sa (evening prayer time). Staff of the Samoan Tourism Authority generally recognise the value of beach fale as a unique tourism product, and they have been supported by NZAID in providing training and financial support to beach fale owners over the past few years. Training in areas such as financial management, health and safety, and service skills is helping to address areas of weakness which exist in the beach fale sector, where many of the owners have limited business experience. Beach fale attract a wide range of clientele, with both Samoan and foreign tourists being very important markets. Samoan guests include couples, families, and youth groups who typically take weekend day trips from Apia to nearby beaches where they pay a small fee to cover use of the beach and a beach fale (which provides shade and a comfortable resting place). Longer stay visitors to beach fale include government and non-governmental agency staff who are sent on retreats to work on their mission statement or review goals and objectives, and family or school groups celebrating a reunion. Foreign visitors are also a diverse group which, rather than being limited to international backpackers, includes a lot of young and middle-aged couples from Australia and New Zealand, surfers, adventurers and ecotourists of all ages, and clientele from up-market hotels like Aggie Grey’s who desire a unique cultural experience for a day or two. The majority of tourists interviewed in this research were extremely positive about beach fale tourism. Typical comments from a beach fale visitor’s book were as follows: ‘Great place’; ‘fantastic food’; ‘wonderful beach’; ‘friendly family’. Many guests commented that they would like to stay longer and/or to return one day. The location of beach fale on what would be prime coastal property with premium values in most parts of the world certainly adds to the value of the fale.One respondent referred to beach fale as ‘5 star hotels the Samoan way’, and many tourists remarked that staying in an open fale gave them a sense of the affinity between culture and nature in Samoan society. Both Samoan and foreign tourists agreed that there were several services that were central to an enjoyable beach fale experience: • clean and well maintained facilities • good meals incorporating local produce • a secure environment • friendly staff. There were few negative perceptions of beach fale, but they are worth mentioning so those operating beach fales or providing training to operators are aware of tourists’ concerns. While they appreciated the relaxed pace of life in Samoa, some tourists felt that the hospitality was ‘too casual’ at times. For example, tourists expressed annoyance that fale which had been booked in advance were given to other guests, and at the time taken to respond to their requests for service or assistance. Newly arrived tourists were sometimes anxious about security or privacy concerns when staying in open fale, but their fears usually abated after a few days. Some tourists felt there was a lack of clarity or inconsistency with pricing practices, thus every operator in a village might charge ST$60 for one night even when the quality of their accommodation and service varied enormously. While a few foreign tourists were concerned that beach fale were now crowding the beach in popular locations, Samoan tourists had no concern about this and felt that there was still space for growth in the overall number of fale. Finally a minority of tourists felt resentful that there were cultural restrictions placed on their activities at certain times (e.g. Sundays); the majority were however very positive about the value of Samoan culture and respectful in their attitude to beach fale rules. Samoa demonstrates that a country with strong indigenous control of the tourism sector can be economically successful. Large-scale development of up-market hotels and resorts based on foreign investment need not be the key objective of Third World governments that wish to maximize their gains from tourism. Indeed, it is probably in Samoa’s interests to stay with small-medium scale tourism development and to cater for a diverse range of tourists, including domestic tourists and those traveling on a budget. Many tourists who come to Samoa are attracted at least partly because of what a locally-controlled tourism industry can offer, namely, low to moderate prices, friendly service, basic accommodation in stunning locations, and a cultural experience.
Keywords: Samoa; Tourism industry; Fields of Research::360000 Policy and Political Science::360200 Policy and Administration::360201 Public policy